2006
DOI: 10.1177/15648265060273s303
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Effectiveness of Community-Based Treatment of Severe Malnutrition

Abstract: Background. There is a long tradition of communitybased rehabilitation for treatment of severe malnutrition: the question is whether it is effective and whether it should be advised for routine health systems.Objective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
126
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(134 citation statements)
references
References 39 publications
5
126
0
1
Order By: Relevance
“…CHWs play an important role in implementing these programs. Outcomes are similar to those provided exclusively at facilities, but at a much lower cost per child and with much higher levels of population coverage (1,6,8,30,83,152).…”
Section: Reduction Of Undernutritionmentioning
confidence: 75%
“…CHWs play an important role in implementing these programs. Outcomes are similar to those provided exclusively at facilities, but at a much lower cost per child and with much higher levels of population coverage (1,6,8,30,83,152).…”
Section: Reduction Of Undernutritionmentioning
confidence: 75%
“…Another review, conducted by Ashworth, et al (5), studied the effectiveness of rehabilitating severely malnourished children in community settings. Effectiveness was defined as mortality of less than 5% or weight gain of more than 5 g/kg/day.…”
Section: Systematic Reviewsmentioning
confidence: 99%
“…A commonly cited reason behind this resistance is the supposed persistence of a high risk of mortality after recovery from SAM once the patient has exited the treatment programme (Ashworth, 2006). Data on the longer term mortality associated with discharge from inpatient therapeutic feeding centres is variable; some studies have reported a cumulative mortality rate of 1 to 1.5 years after discharge of up to 41% (Ashworth, 2006;Chapko et al, 1994;Pecoul et al, 1992;Reneman and Derwig, 1997;Roosmalen-Wiebenga et al, 1987), whilst others have reported lower figures of 2.3% after 12 months of follow up, and 4.1% after 1.5 years of follow up (Bahwere et al, 2008;Khanum et al, 1998). An earlier study reported a mortality of 1.5%, 12 months after discharge among children treated using the domiciliary approach (Khanum et al, 1998).…”
Section: Introductionmentioning
confidence: 99%